A philosophical view on dependence - Gökalp, Nurten (Journal of Dependence, 2017)
When we examine what the addiction is from the point of view of philosophy, it is necessary to look at the concepts of pleasure and passion. Pleasure which can be described as a feeling that is created and woken by something that is generally pleasing is a concept of using for understanding of the biological, psychological and moral life of human beings in the history of philosophy. Passion is defined as violent and constant emotion, strong will and tendency. Passion is a powerful emotion that manages human behavior. The passion is a kind of blindness except which has been focused on its subject or its object . For this reason, in the history of philosophy, most philosophers have taken a negative attitude towards passion and regarded it as a harmful feature. It is thought that the dependent person who shaped his behavior with delight and passion lost his freedom and controlled by what he was addicted to. For the regaining of liberty has been advocated that use of reasoning to pass control the pleasure and passion by many philosophers since the early days of philosophy. This issue is assessed by philosophers with different perspectives. According to them, moving with the mind, not with feelings, will resist the resistance of the passions. As a whole a person with a soul and body, must struggle with his desires and his passions shaped by the body.